Pinpointing the thermal history of lunar basaltic meteorites in a nutshell - Pierre Vonlanthen; Farhang Nabiei; Cyril Cayron; A. Brian Aebersold; Martin Robyr; Mary-Alix Kaczmarek; Othmar Müntener; Philippe Gillet (Nature Communications)
Abstract Native metals of igneous origin are recognized as one of the distinctive features of basalts from the Moon. Our study demonstrates that the tiny Fe-Ni metal blebs nucleated from lunar magma exhibit unanticipated, nutshell-like, crystallographic microstructures, that can be used in conjunction with local variations in chemical compositions to trace the complete thermal history of the host rock. This encompasses rapid cooling on the lunar surface, shock reheating upon impact, and post-shock cooling in the outer space. The Fe-Ni metal blebs indicate that the lava cooled in two stages, first down to 90–160 °C during lunar daytime, and then, to −160 °C during nighttime. Upon shock, the (near-)equilibrium peak temperature of 660–690 °C was reached shortly after release to zero pressure, mainly by thermal conduction from hot vesicular plagioclase. Here, we show that intense shock heating is compatible with the small impact scenario put forward for lunar meteorites and that metals are pioneering full-range geothermometers capable of tracing the complete thermal history of achondritic planetary materials.